(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
The volume "Edizioni Critiche Digitali / Digital Critical Editions. Edizioni a confronto / Comparing editions", editied by Paola Italia and Claudia Bonsi (Roma, Sapienza Università Editrice, 2016, pp. 182) urges the reflection around many conceptual nodes, which emerge from the different positions and the different solicitations exposed in the collected contributions. Some of these are taken into account in the present review.